Analisis Strategi Pemasaran dalam Meningkatkan Bisnis Properti Subsidi di Perumahan Green Jayasampurna Residence - Pupung Purnamasari; Suherdi Maulana; Rida Raodotul Janah; Dheanty Ananda Bilqis (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
This research aims to determine the strengths, weaknesses, opportunities and threats that exist in the marketing strategy for Green Jayasampurna Residence subsidized housing. This research method uses a qualitative approach. The results of the analysis show that the variables that are strengths are the price which is much cheaper and also the quality of the building is good and very satisfying so that it is able to compete with other housing. Currently and in the future, it is certain that the number of house sales will increase from year to year, this is because people's desire for housing is very high so that the need for houses continues to increase. Not only that, the increase in population and the decrease in empty land is also one of the reasons why people prefer housing as an effective and efficient place to live. Marketing in the business world is very competitive with the increasing and developing modern business world today. Thus, the number of business actors is increasing with the aim of meeting the needs and desires of consumers in the form of goods or services. Business actors have the challenge of getting the existing market, namely by improving the quality of buildings by selecting materials. good quality so that good buildings are created with good quality so that consumers are satisfied with the housing offered. If entrepreneurs give special prices to customers who buy a house based on several specific types, this will also increase consumer interest and demand.